Determination of the absolute configuration of compounds bearing chiral quaternary carbon centers using the crystalline sponge method. Issue 7 (30th May 2017) - Sairenji, Shiho; Kikuchi, Takashi; Abozeid, Mohamed Ahmed; Takizawa, Shinobu; Sasai, Hiroaki; Ando, Yuichiro; Ohmatsu, Kohsuke; Ooi, Takashi; Fujita, Makoto
Abstract : The absolute configuration of organic compounds bearing chiral quaternary carbons is determined by the crystalline sponge method. Abstract : Determination of the absolute configuration of chiral tetra-substituted carbon centers is one of the most taxing steps in the enantioselective construction of this structural motif in asymmetric synthesis. Here, we demonstrate that the crystalline sponge method provides an effective way to crystallographically determine the absolute configuration of organic compounds bearing chiral quaternary carbons (including tetra-substituted ones) that are synthesized by recently developed enantioselective catalytic reactions.